Next-generation sequencing in thyroid cancers: do targetable alterations lead to a therapeutic advantage?: A multicenter experience. Issue 25 (25th June 2021) - Moore, Assaf; Bar, Yael; Maurice-Dror, Corinne; Finkel, Inbar; Goldvaser, Hadar; Dudnik, Elizabeth; Goldstein, Daniel A.; Gordon, Noa; Billan, Salem; Gutfeld, Orit; Wolf, Ido; Popovtzer, Aron
Abstract : Abstract: Radioiodine-refractory thyroid cancers (IRTCs) are uncommon and have a poor prognosis. Treatment options for radioiodine-refractory and anaplastic tumors (ATCs) are limited. Although the genomic landscape of thyroid cancer has been studied, there is little evidence on whether next-generation sequencing (NGS) findings translate to tumor control. We analyzed all patients with IRTC and ATC who underwent commercially available NGS in 3 cancer centers. Twenty-two patients were identified, 16 patients with IRTCs and 6 patients with ATCs. Eighteen (82%) had targetable findings in NGS, nine patients were treated accordingly. Median progression-free survival for targeted treatment was 50 months [95% confidence interval (CI95%) 9.8–66.6] and2 months (CI95% 0.2–16.5) for IRTC and ATC, respectively. Of 4 patients who achieved durable responses of 7 to 50 months, 2 are ongoing. The estimated median OS of IRTC receiving targeted treatment was not reached (CI95% 89.7–111.4 months) and was 77.8 months (CI95% 52.5–114.6) for patients treated conventionally ( P = .3). NGS may detect clinically significant genetic alterations and benefit patients with advanced thyroid cancers.